Learning management systems for accreditation approval: A review paper - Tawafak R.M.; Romli A.; Malik S.I.; Alfarsi G. (American Institute of Physics Inc., 2023)
The blended learning (BL) services presented for the academic accreditation process of universities and other educational institutions is a policy that has been used rapidly in the educational area. This process represents a real challenge and a need for institutions to function by the challenges in the ways of development for the attainment of faculty and student satisfaction. The need for learning management systems (LMS) becomes a real advance to control the management of technological development. The purpose of this study is to overcome these challenges and speed up the whole e-learning process in a different manner. The study revealed the existence of an important gap between the important features of blended learning applications and the control management of LMS. The finding shows a systematic analysis of existing technologies and their effects on accreditation checkpoints approval for the underlying conception of the assessment processes involve perspectives that relate to what is now considered valuable or desirable concerning the institution of higher education. 2021 American Institute of Physics Inc.. All rights reserved.